Marriage nullity and family mediation - Miranzo de Mateo, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
This reflection begins with some notes on the conflict and the mediation and on its historical development as a solution to conflicts. The figure of the mediator is described and his possible and opportune intervention before, during and after the canonical process of the marriage nullity.
Keywords: marriage; family; conflicts; mediation; processes of nullity